Contamination of groundwater with per- and polyfluoroalkyl substances (PFAS) from legacy landfills in an urban re-development precinct. (May 2019) - Hepburn, Emily; Madden, Casey; Szabo, Drew; Coggan, Timothy L.; Clarke, Bradley; Currell, Matthew
Abstract: The extent of per- and polyfluoroalkyl substances (PFAS) in groundwater surrounding legacy landfills is currently poorly constrained. Seventeen PFAS were analysed in groundwater surrounding legacy landfills in a major Australian urban re-development precinct. Sampling locations (n = 13) included sites installed directly in waste material and down-gradient from landfills, some of which exhibited evidence of leachate contamination including elevated concentrations of ammonia-N (≤106 mg/L), bicarbonate (≤1, 740 mg/L) and dissolved methane (≤10.4 mg/L). Between one and fourteen PFAS were detected at all sites and PFOS, PFHxS, PFOA and PFBS were detected in all samples. The sum of detected PFAS (∑14 PFAS) varied from 26 ng/L at an ambient background site to 5, 200 ng/L near a potential industrial point-source. PFHxS had the highest median concentration (34 ng/L; range: 2.6–280 ng/L) followed by PFOS (26 ng/L; range: 1.3–4, 800 ng/L), PFHxA (19 ng/L; range: <LOQ – 46 ng/L) and PFOA (12 ng/L; range: 1.7–74 ng/L). Positive correlations between ∑14 PFAS, PFOA and other perfluoroalkyl carboxylic acids (PFCAs) (e.g. PFHxA) with typical leachate indicators including ammonia-N and bicarbonate were observed. In contrast, no such correlations were found with perfluoroalkyl sulfonic acids (PFSAs) (e.g., PFOS and PFHxS). In addition, a strong positive linear correlation (R 2  = 0.69) was found between the proportion of PFOA in the sum of detected perfluorinated alkylated acids (PFOA/∑PFAA) and ammonia-N concentrations in groundwater. This is consistent with previous research showing relatively high PFOA/∑PFAA in municipal landfill leachates, and more conservative behaviour (e.g. less sorption and reactivity) of PFCAs during subsurface transport compared to PFSAs. PFOA/∑PFAA in groundwater may therefore be a useful indicator of municipal landfill-derived PFAA. One site with significantly elevated PFOS and PFHxS concentrations (4, 800 and 280 ng/L, respectively) appears to be affected by point-source industrial contamination, as landfill leachate indicators were absent. Graphical abstract: Image 1 Highlights: Groundwater in Australia's largest urban re-development area was analysed for PFAS. ∑14 PFAS varied from 26 up to 5, 200 ng/L near a potential industrial point-source. PFOA, PFHxA showed positive correlations with landfill leachate indicators. Strong positive linear correlation observed between PFOA/∑PFAA and NH3 N. Groundwater PFOA/∑PFAA may be a useful tracer of municipal landfill-derived PFAS. Abstract : PFAS have been analysed in groundwater surrounding legacy landfills in a major urban re-development precinct in Australia, to better understand their sources, fate and transport.